Цариград в спомените на Ефрем Каранов: илюзии и (раз)очарования - Mevsim, Hüseyin (Lyuboslovie, 2024)
From September 1864 to January 1867, Efrem Karanov (Kratovo, 1852 – Kyustendil, 1927) was a student at the Bulgarian School on the banks of the Golden Horn in the imperial capital. In the last years of his life, he dictated to his loved ones his memories concerning the short, but left a deep impression on his mind and soul time spent at the said school. The memoir, which remained in manuscript, was published almost half a century after the death of its author. “On the Bulgarian church in Constantinople 60 years ago (student memories)” is the most valuable work in the modest literary legacy of Efrem Karanov, which begins with pictures of life in his native Kratovo and continues with the description of the author's journey with his brother and father via Thessaloniki and Kavala to Istanbul. Quite naturally, most pages in the memoir are devoted to the imperial capital. The memory of the past is reconstructed after more than half a century, but in this case the temporal distance is an advantage, as it helps the maximum crystallization of the memory particles; for the sedimentation in the folds of memory of only the most vivid impressions. 12-year-old Efrem builds an ideal image of the capital in advance through mediated ways - from what he reads, hears, tells and listens to from third parties. The present text aims to trace the collapse of illusions, the shattering of the idealized children's idea of the Bulgarian church and the school associated with it in the imperial capital. The disillusionment born after the collision with reality is gradually replaced by a fascination that hides under the veil of the colorful everyday life of the crowded city.